Effect of management system and dietary seasonal variability on environmental efficiency and human net food supply of mountain dairy farming systems - Thomas Zanon; Stefan Hörtenhuber; Greta Fichter; Giovanni Peratoner; Werner Zollitsch; Markus Gatterer; Matthias Gauly (Journal of Dairy Science)
ABSTRACT: Mountain dairy cattle farming systems are pivotal for the economy, as well as for social and environmental aspects. They significantly contribute to rural development, which is currently strongly prioritized in the common European Union agricultural policy; at the same time, they are also increasingly criticized for having a relatively high environmental impact (such as greenhouse gas emissions) per kilogram of product. Consequently, the aim of this study was to assess and compare the environmental efficiency of 2 common alpine dairy farming systems, with a focus on the effects of grazing, considering the seasonal variability in feeding at the individual cow level and farm management over a 3-yr period. This study focuses on alpine farming systems, but can also be considered to effectively represent other topographically disadvantaged mountain areas. We compared an intensively managed and globally dominating production system (high-input) aimed at high milk yield through relatively intensive feeding and the use of the high-yielding dual-purpose Simmental cattle permanently confined in stables, with a forage-based production system (low-input) based on seasonal grazing and the use of the autochthonous dual-purpose breed Tyrolean Grey. For the present analysis, we used a dataset with information on feed intake and diet composition, as well as animal productivity at the individual cow level and farm management data based on multiyear data recording. We quantified 4 impact categories for 3 consecutive years: global warming potential (GWP100), acidification potential (AP), marine eutrophication potential (MEP), and land use (LU; in square meters per year and eco points [Pt], with the latter additionally considering the soil quality index). In addition to being attributed to 1 kg of fat- and protein-corrected milk (FPCM), these impact categories were also related to 1 m2 of on-farm area. Due to limited agronomic options beyond forage production and pasture use in alpine regions, net provision of protein was calculated for both farming systems to assess food supply and quantify the respective food-feed competition. Overall, the low-input farming system had greater environmental efficiency in terms of MEP per kilogram of FPCM, as well as MEP and AP per square meter than the high-input system. Land use was found to be consistently higher for the high-input than for the low-input system, the GWP100 per kilogram of FPCM was lower for the high-input system. Additionally, pasture access had a significant effect on the reduction of environmental impacts. Lastly, the net protein provision was slightly negative for the high-input system and marginally positive for the low-input system, indicating a lower food-feed competition for the latter. Future studies should also address the social and economic aspects of the farming systems in order to offer a comprehensive overview of the 3 key factors necessary for achieving more sustainable farming systems, particularly in disadvantaged marginal regions such as mountain areas.